2008
DOI: 10.1016/j.scriptamat.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube-reinforced magnesium alloy composites

Abstract: This study demonstrates the ability to fabricate lightweight, ductile but mechanically strong magnesium alloy (AZ91D) composites by introducing a small number of high crystalline multi-walled carbon nanotubes. It is demonstrated that 1 % of relatively short and straight carbon nanotubes distributed homogeneously on the outer surface of magnesium powders act as an effective reinforcing filler to prevent deformation, thereby contributing to the enhanced tensile strength of magnesium alloy composites (e.g., from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
73
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(95 citation statements)
references
References 26 publications
4
73
0
3
Order By: Relevance
“…Previous studies indicated characteristics of the metal matrix composites (MMCs) reinforced with CNTs, where industrial metals such as aluminum, magnesium, nickel, copper and their alloys were used [5][6][7][8][9][10][11][12][13][14]. Titanium (Ti) and titanium alloy are also interested as the matrix material because they are widely used in various industrial applications, for example, automotive, motorcycles, and airplane industries due to their high specific strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated characteristics of the metal matrix composites (MMCs) reinforced with CNTs, where industrial metals such as aluminum, magnesium, nickel, copper and their alloys were used [5][6][7][8][9][10][11][12][13][14]. Titanium (Ti) and titanium alloy are also interested as the matrix material because they are widely used in various industrial applications, for example, automotive, motorcycles, and airplane industries due to their high specific strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several significant studies showed that the introduction of carbon nanotubes resulted in lightweight composites with enhanced mechanical strength. [7][8][9][10][11] In particular, we proved that the short, linear and well-ordered MWNTs directly contributed to 25 and 11 % increases in the elastic modulus and tensile strength of magnesium alloy composites, respectively. 11 From these results, we envisage that MWNTs-filled magnesium composites are possibly the best candidates for constructing lightweight materials for automobiles, always considering an energy-efficient environment.…”
mentioning
confidence: 62%
“…[7][8][9][10][11] In particular, we proved that the short, linear and well-ordered MWNTs directly contributed to 25 and 11 % increases in the elastic modulus and tensile strength of magnesium alloy composites, respectively. 11 From these results, we envisage that MWNTs-filled magnesium composites are possibly the best candidates for constructing lightweight materials for automobiles, always considering an energy-efficient environment. We believe that nanotube-filled magnesium alloy composites could replace aluminum alloys in some commercial markets and will boost the replacement of engineering plastics where the components with lightweight, hardness and mechanical strength are required.…”
mentioning
confidence: 62%
See 2 more Smart Citations